I. Hofmeyr, The portable Bunyan: a transnational history of The Pilgrim's Progress - B. A. Zuiddam (Acta Theologica)
From text: As I was about to receive The portable Bunyan for review purposes, I was looking forward to some collected or condensed work by the great Puritan Baptist.